Oxalic Acid From Sesbania rostrata Seed Exudates Mediates the Chemotactic Response of Azorhizobium caulinodans ORS571 Using Multiple Strategies - Liu, Xiaolin; Zhang, Kaiye; Liu, Yanan; Xie, Zhihong; Zhang, Chengsheng (Frontiers in Microbiology, 2019)
Chemotaxis toward seed exudates is important in the establishment of microbe–plant associations. The objective of this work was to explore whether organic acids from the seed exudates of Sesbania rostrata play a role in recruiting Azorhizobium caulinodans ORS571 in the plant rhizosphere. High-performance liquid chromatography (HPLC) was used to analyze the organic acid content in seed exudates of S. rostrata and to further determine their roles in A. caulinodans growth and chemotactic response. Succinic, acetic, citric, oxalic, and lactic acids were the most abundant, and, except for oxalic acid, they could support A. caulinodans growth as the sole carbon source. TlpA1, a transmembrane chemoreceptor, was found to be involved in the chemotactic response to these organic acids. Oxalic acid played a direct role in the chemotactic response, but it also played an indirect role by promoting or inhibiting the chemotactic response toward other chemoeffectors. Furthermore, the indirect role of oxalic acid on other chemoeffectors was concentration-dependent. The effect of oxalic acid at different concentrations on host root colonization was also determined. By using different strategies, oxalic acid appears to play a major role in the early steps of the association of A. caulinodans and its host plant.